Disbelief 101 : a young person's guide to atheism - Hitchcock, S. C.; White, Leslie (Tucson, Ariz : See Sharp Press, 2009)
Filled with wit, humor, and clear metaphor, this exploration into atheism is written specifically for young adults, though any adult interested in learning more about atheism will find value within. Not just focused on atheism, this crash course in logical thinking addresses the issues of indoctrination, whether it be religious, political, or commercial, and makes the case that morality is created through reasoning and logic, not through divine communication. Many hot topics are touched upon, such as traditional arguments for God's existence, the relationship of evolution and religious belief
Front Cover ; Copyright ; Contents ; Introduction (by Tom Flynn); Acknowledgments; Preface; 1. The Invisible Flying Clown; 2. Atheism as "Belief"; 3. Faith: A False Virtue; 4. The Suicide King- Arguments for God's Existence; 5. Evolution and Religion; 6. Two Columns: Science and Faith; 7. The Rock Star Principle- Why Are We Here?; 8. Does Anybody Ever Read This Thing? (The Bible, That Is); 9. Feelings as "Proof"; 10. Let the Buyer Beware; 11. The Darwinian God; 12. Religious Indoctrination of Children Is Child Abuse; Bibliography; Index; Back Cover
Includes bibliographical references and index
Keywords: Atheism -- Juvenile literature; Critical thinking -- Juvenile literature; Skepticism -- Juvenile literature